2008
DOI: 10.1177/003335490812300206
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Patterns and Smoking Behaviors after a Large Tobacco Tax Increase: A Study of Chinese Americans Living in New York City

Abstract: SYNOPSISObjectives. Tobacco taxes are one of the most effective policy interventions to reduce tobacco use. Tax avoidance, however, lessens the public health benefits of higher-priced cigarettes. Few studies examine responses to cigarette tax policies, particularly among high-risk minority populations. This study examined the prevalence and correlates of tax avoidance and changes in smoking behaviors among Chinese American smokers in New York City after a large tax increase.Methods. We conducted a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies were in adolescents or young adults 20,25,31 and the others were based on adults. Three studies included primarily men, 21,26,32 including one based on smokers with a medical condition. 32 …”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Taxes and higher prices for cigarettes consistently reduce consumption (23,86,122). Similarly, when taxes are placed on alcohol, consumption decreases (142).…”
Section: Limit Marketing Of Ssbs and Minimize Marketing's Impact On Cmentioning
confidence: 99%